El nuevo marco legal del Sistema Gallego de Cooperación al Desarrollo: comentarios sobre la Ley 3/2003 de 19 de junio - Teijo García, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
The article displays the basic features of the Galician Development Co-operation Law, focusing on the modifications experienced by the text during the parliamentary proceeding, trying to compare the solutions that incorporates with the dispositions gathered in analogous norms of other spanish autonomies. Finnally it tries to contrast the contents of the legislative text with the precarious reality of the Galician co-operations system.